A core-shell structure Au@Ni-MOF composite material, a preparation method and application thereof

CN117448882BActive Publication Date: 2026-10-27TAIYUAN UNIVERSITY OF TECHNOLOGY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311205397.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-09-19
Publication Date
2026-10-27
Estimated Expiration
2043-09-19

AI Technical Summary

Technical Problem

但是,该Ni-MOF存在可见光吸收能力差的问题,是制约该材料析氢性能的关键因素

Benefits of technology

[0035]本发明提供了一种核壳结构材料及其制备方法,该核壳结构材料为Au@Ni-MOF,其中作为核的材料是Au纳米颗粒,作为壳的材料是片状Ni-MOF,整体构成花球状。其制备方法是:将PVP修饰的金纳米颗粒的甲醇溶液与二甲基咪唑的甲醇溶液混合,然后超声得到均相混合溶液;将上述混合溶液加入到硝酸镍六水合物的甲醇溶液中,充分搅拌过后,得到Au@Ni-MOF前驱体溶液;将Au@Ni-MOF前驱体溶液进行溶剂热反应,反应结束后,进行清洗离心,得到核壳结构的Au@Ni-MOF复合材料。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117448882B_ABST
    Figure CN117448882B_ABST
Patent Text Reader

Abstract

The application provides a core-shell structure Au@Ni-MOF composite material and a preparation method and application thereof. The material serving as the core in the core-shell structure material is Au nanoparticles, the material serving as the shell is flaky Ni-MOF, and the whole constitutes a flower ball. The preparation method of the composite material comprises the following steps: preparation of a PVP modified gold nanoparticle hydrosol; preparation of an Au@Ni-MOF composite material precursor solution; and preparation of a core-shell structure Au@Ni-MOF composite material. Compared with inorganic semiconductor photocatalysts, the core-shell structure Au@Ni-MOF composite material provided by the application effectively enhances the visible light absorption capacity of the material due to the presence of gold nanoparticles, the overall flower-shaped morphology structure makes it have more exposed catalytically active sites, and the synergistic effect of the gold nanoparticles and the flaky Ni-MOF enables the catalyst material to effectively realize photoelectrocatalytic water splitting to produce hydrogen, and the catalyst material can be applied to the field of new energy conversion.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of catalysis technology, specifically relating to a core-shell structure Au@Ni-MOF composite material for photoelectrocatalytic water splitting to produce hydrogen, its preparation method, and its application. Background Technology

[0002] Due to the increasingly severe energy crisis and environmental pollution, humanity urgently needs to develop green pathways to produce new clean energy sources. Scientists have proposed photocatalytic / electrocatalytic water splitting for hydrogen production. However, current materials used for photocatalytic / electrocatalytic hydrogen production are mainly inorganic semiconductors, whose light absorption range is primarily concentrated in the ultraviolet region, resulting in insufficient hydrogen production performance.

[0003] MOFs (metal-organic frameworks) are porous materials composed of metal nodes and organic ligands. Different MOF materials can be obtained by combining different metal nodes and organic ligands. Currently, a large number of MOF materials have been developed. Due to their high specific surface area, large porosity, excellent structural designability, and functional tunability, they are widely used in gas adsorption and separation, pharmaceutical delivery, catalysis, and sensing. Furthermore, due to the excellent properties of MOF materials, their design as electrode materials has also attracted widespread attention.

[0004] The properties of MOF materials determine their applications. Among various MOF materials, Ni-MOF, formed by the combination of Ni ions and dimethylimidazole, possesses a flower-like morphology assembled from 2D nanosheets, resulting in a large specific surface area and abundant exposed surface active sites. Furthermore, the Ni ions at the metal nodes can also serve as hydrogen evolution active sites, making it suitable as a photoelectrode material for photoelectrochemical hydrogen evolution. However, the poor visible light absorption of Ni-MOF is a key factor limiting its hydrogen evolution performance.

[0005] Therefore, there is a need to provide an improved technical solution that addresses the shortcomings of the existing technology. Summary of the Invention

[0006] To address the shortcomings of the existing technologies, the present invention aims to provide a core-shell structured Au@Ni-MOF composite material for photoelectrocatalytic water splitting to produce hydrogen, its preparation method, and its applications.

[0007] To achieve the above objectives, the present invention provides the following technical solution:

[0008] This invention provides a method for preparing a core-shell structured Au@Ni-MOF composite material, comprising the following steps:

[0009] S1, Preparation of PVP-modified gold nanoparticle hydrosol:

[0010] Prepare aqueous solutions of chloroauric acid, sodium citrate, and PVP separately for later use.

[0011] The aqueous solution of chloroauric acid was stirred and heated to boiling, and then an aqueous solution of sodium citrate was added. Stirring was continued to obtain a hydrosol of gold nanoparticles.

[0012] PVP aqueous solution was added to gold nanoparticle hydrosol and stirred to obtain PVP-modified gold nanoparticle hydrosol.

[0013] Preparation of S2 and Au@Ni-MOF composite precursor solutions:

[0014] Take the PVP-modified gold nanoparticle hydrosol, centrifuge and wash with methanol, and finally disperse it in methanol to obtain a PVP-modified gold nanoparticle methanol solution for later use.

[0015] Prepare 2-methylimidazolium methanol solution and nickel nitrate methanol solution for later use;

[0016] A methanol solution of PVP-modified gold nanoparticles was mixed with a methanol solution of 2-methylimidazole and then subjected to ultrasonic treatment to obtain a 2-methylimidazole-Au methanol solution.

[0017] 2-Methylimidazolium-Au methanol solution was added to nickel nitrate methanol solution and stirred continuously to obtain Au@Ni-MOF composite material precursor solution;

[0018] S3. Preparation of core-shell structured Au@Ni-MOF composite materials:

[0019] The Au@Ni-MOF composite material precursor solution was subjected to a hydrothermal reaction. After the hydrothermal reaction was completed, it was centrifuged and washed to obtain the final product.

[0020] Preferably, the mass concentration of the chloroauric acid aqueous solution in S1 is 0.005-0.01%; the mass concentration of the sodium citrate aqueous solution is 1-2%.

[0021] The PVP aqueous solution was prepared using PVP-K30, which has a relative molecular mass of 40,000 and a mass concentration of 2-3%.

[0022] Preferably, the mass concentration of the sodium citrate aqueous solution is 1%.

[0023] Preferably, the volume ratio of chloroauric acid aqueous solution to sodium citrate aqueous solution in S1 is 1000:7, and the volume ratio of gold nanoparticle hydrosol to PVP aqueous solution is 50:1.

[0024] Preferably, the stirring time after adding sodium citrate to S1 is 10-20 min; and the stirring time after adding PVP aqueous solution is 20-28 h.

[0025] Preferably, the volume ratio of the PVP-modified gold nanoparticle hydrosol to the 2-methylimidazolium methanol solution in S2 is 2-5:1.

[0026] Preferably, the mass concentration of the 2-methylimidazolium methanol solution in S2 is 2.5-3%, and the mass concentration of the nickel nitrate methanol solution is 1-1.5%.

[0027] The volume ratio of 2-methylimidazolium methanol solution to nickel nitrate methanol solution in S2 is 3:4.

[0028] Preferably, in S2, the centrifugation speed is 11000 rpm, the centrifugation time is 5 min, the ultrasonic treatment time is 10-25 min, and the stirring time is 0.5-2 h.

[0029] Preferably, the hydrothermal reaction temperature in S3 is 130-150℃, and the reaction time is 10-14h;

[0030] In S3, the centrifugation speed is 9000 rpm and the centrifugation time is 5 min.

[0031] More preferably, the hydrothermal reaction temperature in S3 is 140°C and the reaction time is 12h.

[0032] This invention provides a core-shell structured Au@Ni-MOF composite material, which is prepared by the aforementioned preparation method.

[0033] This invention provides the application of a core-shell structured Au@Ni-MOF composite material in the preparation of photoelectrode materials for photoelectrochemical water splitting to produce hydrogen.

[0034] Beneficial effects:

[0035] This invention provides a core-shell structured material and its preparation method. The core-shell structured material is Au@Ni-MOF, wherein the core material is Au nanoparticles and the shell material is sheet-like Ni-MOF, forming an overall flower-like shape. The preparation method is as follows: a methanol solution of PVP-modified gold nanoparticles is mixed with a methanol solution of dimethylimidazole, and then ultrasonicated to obtain a homogeneous mixed solution; the above mixed solution is added to a methanol solution of nickel nitrate hexahydrate, and after thorough stirring, an Au@Ni-MOF precursor solution is obtained; the Au@Ni-MOF precursor solution is subjected to a solvothermal reaction, and after the reaction is completed, it is washed and centrifuged to obtain the core-shell structured Au@Ni-MOF composite material.

[0036] This invention utilizes a chemical reduction method to prepare gold nanoparticles and then constructs a core-shell structured Au@Ni-MOF composite material via a hydrothermal method. The gold nanoparticles exhibit excellent light absorption in the visible light region, effectively addressing the poor light absorption capacity of Ni-MOF. Due to the numerous exposed surface active sites on the plate-like Ni-MOF, photoelectrochemical water splitting for hydrogen production can be effectively achieved. The Au@Ni-MOF composite material combines the superior properties of Au nanoparticles and plate-like Ni-MOF, resulting in a composite material with excellent photoelectrochemical water splitting hydrogen production performance, which can be applied in the field of new energy conversion.

[0037] Compared with inorganic semiconductor photocatalysts, the core-shell structure Au@Ni-MOF composite material provided by this invention effectively enhances the visible light absorption capacity of the material due to the presence of gold nanoparticles. The overall flower-like morphology structure gives it more exposed catalytic active sites. The synergistic effect of gold nanoparticles and sheet-like Ni-MOF enables this catalyst material to effectively achieve photoelectrochemical water splitting to produce hydrogen. Attached Figure Description

[0038] The accompanying drawings, which form part of this application, are used to provide a further understanding of the invention. The illustrative embodiments of the invention and their descriptions are used to explain the invention and do not constitute an undue limitation of the invention. Wherein:

[0039] Figure 1 This is a scanning electron microscope image (×1μm) of the composite material prepared in Example 1 of the present invention.

[0040] Figure 2 This is a transmission electron microscope (TEM) image (×300nm) of the composite material prepared in Example 1 of the present invention.

[0041] Figure 3 These are the ultraviolet-visible absorption spectra of the composite materials and gold nanoparticles prepared in Example 1 and Comparative Example 1 of this invention.

[0042] Figure 4 This is a bar chart showing the photoelectrocatalytic hydrogen production performance of the composite materials prepared in Example 1 and Comparative Example 1 of this invention. Detailed Implementation

[0043] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of them. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention are within the scope of protection of the present invention.

[0044] The present invention will now be described in detail with reference to embodiments. It should be noted that, unless otherwise specified, the embodiments and features described in the embodiments of the present invention can be combined with each other.

[0045] This invention addresses the existing problems by providing a method for preparing a core-shell structured Au@Ni-MOF composite material, comprising the following steps:

[0046] S1, Preparation of PVP-modified gold nanoparticle hydrosol:

[0047] Chloroauric acid trihydrate was dissolved in deionized water to obtain an aqueous solution of chloroauric acid.

[0048] Dissolve sodium citrate in deionized water to obtain an aqueous solution of sodium citrate;

[0049] Dissolve PVP-K30 in deionized water to obtain a PVP aqueous solution;

[0050] The aqueous solution of chloroauric acid was stirred and heated to boiling, and then an aqueous solution of sodium citrate was added. Stirring was continued to obtain a hydrosol of gold nanoparticles.

[0051] PVP aqueous solution was added to gold nanoparticle hydrosol and stirred to obtain PVP-modified gold nanoparticle hydrosol.

[0052] Preparation of S2 and Au@Ni-MOF composite precursor solutions:

[0053] Take the PVP-modified gold nanoparticle hydrosol, centrifuge and wash with methanol, and finally disperse it in methanol to obtain a PVP-modified gold nanoparticle methanol solution.

[0054] Dissolve 2-methylimidazole in methanol to obtain a 2-methylimidazole methanol solution;

[0055] A methanol solution of PVP-modified gold nanoparticles was mixed with a methanol solution of 2-methylimidazole and then subjected to ultrasonic treatment to obtain a 2-methylimidazole-Au methanol solution.

[0056] Nickel nitrate hexahydrate was dissolved in methanol to obtain a nickel nitrate methanol solution;

[0057] 2-Methylimidazolium-Au methanol solution was added to nickel nitrate methanol solution and stirred continuously to obtain Au@Ni-MOF composite material precursor solution;

[0058] S3. Preparation of core-shell structured Au@Ni-MOF composite materials:

[0059] The Au@Ni-MOF composite material precursor solution was subjected to a hydrothermal reaction. After the hydrothermal reaction was completed, it was centrifuged and washed to obtain the final product.

[0060] The gold nanoparticles prepared in this invention have a size concentrated between 30-50 nm. Their small size results in high surface energy, making them prone to aggregation. Modifying the surface of the gold nanoparticles with PVP can effectively prevent aggregation during storage and the synthesis of composite materials. Dimethylimidazole, as an organic ligand, can coordinate with various metal ions, and it is inexpensive and readily available.

[0061] In a preferred embodiment of the present invention, the mass concentration of the chloroauric acid aqueous solution in S1 is 0.005-0.01% (e.g., 0.005%, 0.006%, 0.007%, 0.008%, or 0.01%); the mass concentration of the sodium citrate aqueous solution is 1-2% (e.g., 1%, 1.4%, 1.6%, 1.8%, or 2%).

[0062] The relative molecular mass of PVP-K30 is 40,000, and the mass concentration of PVP aqueous solution is 2-3% (e.g., 2%, 2.4%, 2.6%, 2.8% or 3%).

[0063] In a preferred embodiment of the present invention, the mass concentration of the sodium citrate aqueous solution is 1%.

[0064] In a preferred embodiment of the present invention, the volume ratio of chloroauric acid aqueous solution to sodium citrate aqueous solution in S1 is 1000:7, and the volume ratio of gold nanoparticle hydrosol to PVP aqueous solution is 50:1.

[0065] In a preferred embodiment of the present invention, the stirring time after adding sodium citrate in S1 is 10-20 min (e.g., 10 min, 15 min, 18 min or 20 min); the stirring time after adding PVP aqueous solution is 20-28 h (e.g., 20 h, 24 h, 26 h or 28 h).

[0066] In a preferred embodiment of the present invention, the volume ratio of the PVP-modified gold nanoparticle hydrosol to the 2-methylimidazolium methanol solution in S2 is 2-5:1 (e.g., 2:1, 3:1, 4:1 or 5:1).

[0067] In a preferred embodiment of the present invention, the mass concentration of the 2-methylimidazolium methanol solution in S2 is 2.5-3% (e.g., 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, or 3%), and the mass concentration of the nickel nitrate methanol solution is 1-1.5% (e.g., 1%, 1.2%, 1.4%, or 1.5%).

[0068] The volume ratio of 2-methylimidazolium methanol solution to nickel nitrate methanol solution in S2 is 3:4.

[0069] The concentration and amount of sodium citrate significantly affect the synthesis of gold nanoparticles, and the properties of gold nanoparticles of different sizes also vary. The volume ratio of chloroauric acid solution to sodium citrate solution, as well as the mass ratio of solute to solvent when preparing the two solutions, are all aimed at obtaining gold nanoparticles within a specific size range. Figure 2 As can be seen, the size distribution of gold nanoparticles is between 30 and 50 nanometers.

[0070] In a preferred embodiment of the present invention, the centrifugation speed in S2 is 11000 rpm, the centrifugation time is 5 min, the ultrasonic treatment time is 10-25 min (e.g., 10 min, 15 min, 20 min or 25 min), and the stirring time is 0.5-2 h (e.g., 0.5 h, 1 h, 1.5 h or 2 h).

[0071] In a preferred embodiment of the present invention, the temperature of the hydrothermal reaction in S3 is 130-150℃ (e.g., 130℃, 140℃ or 150℃), and the reaction time is 10-14h (e.g., 10h, 12h or 14h); the centrifugation speed in S3 is 9000rpm, and the centrifugation time is 5min.

[0072] This invention provides a core-shell structured Au@Ni-MOF composite material, which is prepared by the aforementioned preparation method.

[0073] This invention provides an application of a core-shell structured Au@Ni-MOF composite material in photoelectrocatalytic water splitting for hydrogen production.

[0074] The following detailed description of a core-shell structured Au@Ni-MOF composite material, its preparation method, and its application are illustrated through specific embodiments.

[0075] Example 1

[0076] The preparation method of the core-shell structured Au@Ni-MOF composite material provided in this embodiment includes the following steps:

[0077] S1, Preparation of PVP-modified gold nanoparticle hydrosol:

[0078] Dissolve 10 mg of chloroauric acid trihydrate in 100 mL of deionized water to obtain an aqueous solution of chloroauric acid.

[0079] Dissolve 0.1g of sodium citrate in 10mL of deionized water to obtain an aqueous solution of sodium citrate;

[0080] Dissolve 255 mg of polyvinylpyrrolidone (PVP-K30) in 10 mL of deionized water to obtain a PVP aqueous solution;

[0081] Take 100 mL of chloroauric acid aqueous solution, stir and heat to boiling, then quickly add 0.7 mL of sodium citrate aqueous solution and continue stirring for 15 min to obtain gold nanoparticle hydrosol.

[0082] Add 2 mL of PVP aqueous solution to 100 mL of gold nanoparticle hydrosol and continue stirring for 24 h to obtain PVP-modified gold nanoparticle hydrosol.

[0083] Preparation of S2 and Au@Ni-MOF composite precursor solutions:

[0084] Take 50 mL of the PVP-modified gold nanoparticle hydrosol obtained in S1, centrifuge (centrifugation speed 11000 rpm, centrifugation time 5 min), wash with methanol, and finally disperse in 5 mL of methanol to obtain a PVP-modified gold nanoparticle methanol solution.

[0085] Dissolve 0.328 g of dimethylimidazole in 15 mL of methanol to obtain a 2-methylimidazole methanol solution;

[0086] 5 mL of PVP-modified gold nanoparticle methanol solution was mixed with 15 mL of 2-methylimidazole methanol solution and sonicated for 15 min to obtain 2-methylimidazole-Au methanol solution.

[0087] Dissolve 0.29 g of nickel nitrate hexahydrate in 20 mL of methanol to obtain a nickel nitrate methanol solution;

[0088] Add 20 mL of 2-methylimidazolium-Au methanol solution to 20 mL of nickel nitrate methanol solution and stir continuously for 1 h to obtain Au@Ni-MOF composite material precursor solution;

[0089] S3. Preparation of core-shell structured Au@Ni-MOF composite materials:

[0090] The Au@Ni-MOF composite precursor solution obtained in S2 was reacted at 140℃ for 12h. After the hydrothermal reaction was completed, centrifugation was performed (centrifugation speed of 9000 rpm, centrifugation time of 5 min) to obtain the composite material, which is a core-shell structure Au@Ni-MOF.

[0091] Example 2

[0092] The preparation method of the core-shell structured Au@Ni-MOF composite material provided in this embodiment includes the following steps:

[0093] S1, Preparation of PVP-modified gold nanoparticle hydrosol:

[0094] Dissolve 10 mg of chloroauric acid trihydrate in 100 mL of deionized water to obtain an aqueous solution of chloroauric acid.

[0095] Dissolve 0.1g of sodium citrate in 10mL of deionized water to obtain an aqueous solution of sodium citrate;

[0096] Dissolve 255 mg of polyvinylpyrrolidone in 10 mL of deionized water to obtain a PVP aqueous solution.

[0097] Take 100 mL of chloroauric acid aqueous solution, stir and heat to boiling, then quickly add 0.7 mL of sodium citrate aqueous solution and continue stirring for 10 min to obtain gold nanoparticle hydrosol;

[0098] Add 2 mL of PVP aqueous solution to 100 mL of gold nanoparticle hydrosol and continue stirring for 24 h to obtain PVP-modified gold nanoparticle hydrosol.

[0099] Preparation of S2 and Au@Ni-MOF composite precursor solutions:

[0100] Take 30 mL of the PVP-modified gold nanoparticle hydrosol obtained in S1, centrifuge (centrifugation speed 11000 rpm, centrifugation time 5 min), wash with methanol, and finally disperse in 5 mL of methanol to obtain a PVP-modified gold nanoparticle methanol solution.

[0101] Dissolve 0.328 g of dimethylimidazole in 15 mL of methanol to obtain a 2-methylimidazole methanol solution;

[0102] 5 mL of PVP-modified gold nanoparticle methanol solution was mixed with 15 mL of 2-methylimidazole methanol solution and sonicated for 15 min to obtain 2-methylimidazole-Au methanol solution.

[0103] Dissolve 0.29 g of nickel nitrate hexahydrate in 20 mL of methanol to obtain a nickel nitrate methanol solution;

[0104] Add 20 mL of 2-methylimidazolium-Au methanol solution to 20 mL of nickel nitrate methanol solution and stir continuously for 1 h to obtain Au@Ni-MOF composite material precursor solution;

[0105] S3. Preparation of core-shell structured Au@Ni-MOF composite materials:

[0106] The Au@Ni-MOF composite precursor solution obtained in S2 was reacted at 140℃ for 12h. After the hydrothermal reaction was completed, centrifugation was performed (centrifugation speed of 9000 rpm, centrifugation time of 5 min) to obtain the composite material, which is a core-shell structure Au@Ni-MOF.

[0107] Testing revealed that the material obtained in this embodiment is a core-shell structured Au@Ni-MOF composite material.

[0108] Example 3

[0109] The preparation method of the core-shell structured Au@Ni-MOF composite material provided in this embodiment includes the following steps:

[0110] S1, Preparation of PVP-modified gold nanoparticle hydrosol:

[0111] Dissolve 9 mg of chloroauric acid trihydrate in 100 mL of deionized water to obtain an aqueous solution of chloroauric acid.

[0112] Dissolve 0.1g of sodium citrate in 10mL of deionized water to obtain an aqueous solution of sodium citrate;

[0113] Dissolve 200 mg of polyvinylpyrrolidone in 10 mL of deionized water to obtain a PVP aqueous solution;

[0114] Stir and heat 100 mL of chloroauric acid aqueous solution to boiling, then quickly add 0.7 mL of sodium citrate aqueous solution and continue stirring for 20 min to obtain gold nanoparticle hydrosol.

[0115] Add 2 mL of PVP aqueous solution to 100 mL of gold nanoparticle hydrosol and continue stirring for 28 h to obtain PVP-modified gold nanoparticle hydrosol.

[0116] Preparation of S2 and Au@Ni-MOF composite precursor solutions:

[0117] Take 70 mL of the PVP-modified gold nanoparticle hydrosol obtained in S1, centrifuge (centrifugation speed 11000 rpm, centrifugation time 5 min), wash with methanol, and finally disperse in 5 mL of methanol to obtain a PVP-modified gold nanoparticle methanol solution.

[0118] Dissolve 0.328 g of dimethylimidazole in 15 mL of methanol to obtain a 2-methylimidazole methanol solution;

[0119] 5 mL of PVP-modified gold nanoparticle methanol solution was mixed with 15 mL of 2-methylimidazole methanol solution and sonicated for 25 min to obtain 2-methylimidazole-Au methanol solution.

[0120] Dissolve 0.29 g of nickel nitrate hexahydrate in 20 mL of methanol to obtain a nickel nitrate methanol solution;

[0121] Add 20 mL of 2-methylimidazolium-Au methanol solution to 20 mL of nickel nitrate methanol solution and stir continuously for 1 h to obtain Au@Ni-MOF composite material precursor solution;

[0122] S3. Preparation of core-shell structured Au@Ni-MOF composite materials:

[0123] The Au@Ni-MOF composite precursor solution obtained in S2 was reacted at 140℃ for 12h. After the hydrothermal reaction was completed, centrifugation was performed (centrifugation speed of 9000 rpm, centrifugation time of 5 min) to obtain the composite material, which is a core-shell structure Au@Ni-MOF.

[0124] Testing revealed that the material obtained in this embodiment is a core-shell structured Au@Ni-MOF composite material.

[0125] Example 4

[0126] The preparation method of the core-shell structured Au@Ni-MOF composite material provided in this embodiment includes the following steps:

[0127] S1, Preparation of PVP-modified gold nanoparticle hydrosol:

[0128] Dissolve 9 mg of chloroauric acid trihydrate in 100 mL of deionized water to obtain an aqueous solution of chloroauric acid.

[0129] Dissolve 0.1g of sodium citrate in 10mL of deionized water to obtain an aqueous solution of sodium citrate;

[0130] Dissolve 255 mg of polyvinylpyrrolidone in 10 mL of deionized water to obtain a PVP aqueous solution.

[0131] Stir and heat 100 mL of chloroauric acid aqueous solution to boiling, then quickly add 0.7 mL of sodium citrate aqueous solution and continue stirring for 15 min to obtain gold nanoparticle hydrosol.

[0132] Add 2 mL of PVP aqueous solution to 100 mL of gold nanoparticle hydrosol and continue stirring for 24 h to obtain PVP-modified gold nanoparticle hydrosol.

[0133] Preparation of S2 and Au@Ni-MOF composite precursor solutions:

[0134] Take 50 mL of the PVP-modified gold nanoparticle hydrosol obtained in S1, centrifuge (centrifugation speed 11000 rpm, centrifugation time 5 min), wash with methanol, and finally disperse in 5 mL of methanol to obtain a PVP-modified gold nanoparticle methanol solution.

[0135] Dissolve 0.328 g of dimethylimidazole in 15 mL of methanol to obtain a 2-methylimidazole methanol solution;

[0136] 5 mL of PVP-modified gold nanoparticle methanol solution was mixed with 15 mL of 2-methylimidazole methanol solution and sonicated for 10 min to obtain 2-methylimidazole-Au methanol solution.

[0137] Dissolve 0.29 g of nickel nitrate hexahydrate in 20 mL of methanol to obtain a nickel nitrate methanol solution;

[0138] 20 mL of 2-methylimidazolium-Au methanol solution was added to 20 mL of nickel nitrate methanol solution, and the mixture was stirred continuously for 0.5 h to obtain the Au@Ni-MOF composite material precursor solution.

[0139] S3. Preparation of core-shell structured Au@Ni-MOF composite materials:

[0140] The Au@Ni-MOF composite precursor solution obtained in S2 was reacted at 140℃ for 14h. After the hydrothermal reaction was completed, centrifugation was performed (centrifugation speed of 9000 rpm, centrifugation time of 5 min) to obtain the composite material, which is a core-shell structure Au@Ni-MOF.

[0141] Testing revealed that the material obtained in this embodiment is a core-shell structured Au@Ni-MOF composite material.

[0142] Example 5

[0143] The only difference between this embodiment and Embodiment 1 is that the stirring time after adding the PVP aqueous solution in S1 is 20 hours; the other methods and steps are the same as in Embodiment 1.

[0144] Example 6

[0145] The only difference between this embodiment and embodiment 1 is that the ultrasonic treatment time in S2 is 10 min and the stirring time is 2 h. The other methods and steps are the same as in embodiment 1.

[0146] Example 7

[0147] The only difference between this embodiment and Embodiment 1 is that the hydrothermal reaction temperature in S3 is 130°C, while the other methods and steps are the same as in Embodiment 1.

[0148] Example 8

[0149] The only difference between this embodiment and Embodiment 1 is that the hydrothermal reaction time in S3 is 150°C, while the other methods and steps are the same as in Embodiment 1.

[0150] Example 9

[0151] The only difference between this embodiment and Embodiment 1 is that the hydrothermal reaction time in S3 is 10 hours; the other methods and steps are the same as in Embodiment 1.

[0152] Comparative Example 1

[0153] The difference between this comparative example and Example 1 is that it does not involve the loading of gold nanoparticles, resulting in a Ni-MOF composite material. The preparation method of this Ni-MOF composite material includes the following steps:

[0154] Preparation of S1 and Ni-MOF composite precursor solutions:

[0155] Dissolve 0.328 g of dimethylimidazole in 20 mL of methanol to obtain a 2-methylimidazole methanol solution;

[0156] Dissolve 0.29 g of nickel nitrate hexahydrate in 20 mL of methanol to obtain a nickel nitrate methanol solution;

[0157] Add 20 mL of 2-methylimidazolium methanol solution to 20 mL of nickel nitrate methanol solution and stir continuously for 1 h to obtain Ni-MOF material precursor solution;

[0158] S2. Preparation of flower-like Ni-MOF materials:

[0159] The Ni-MOF precursor solution obtained in S1 was reacted at 140℃ for 12 hours. After the hydrothermal reaction was completed, it was centrifuged and washed (centrifugation speed was 9000 rpm, centrifugation time was 5 min) to obtain the material, which is flower-shaped Ni-MOF.

[0160] Comparative Example 2

[0161] The only difference between this comparative example and Example 1 is that the hydrothermal reaction temperature in step S3 is 100°C, while the other methods and steps are the same as in Example 1.

[0162] Comparative Example 3

[0163] The only difference between this comparative example and Example 1 is that the hydrothermal reaction time in step S3 is 8 hours, while the other methods and steps are the same as in Example 1.

[0164] Comparative Example 4

[0165] The only difference between this comparative example and Example 1 is that in step S2, the volume of the PVP-modified gold nanoparticle hydrosol is 5 mL (i.e., the volume ratio of the PVP-modified gold nanoparticle hydrosol to the 2-methylimidazolium methanol solution is 1:3). The other methods and steps are the same as in Example 1.

[0166] Comparative Example 5

[0167] The only difference between this comparative example and Example 1 is that in step S2, the volume of the PVP-modified gold nanoparticle hydrosol is 120 mL (i.e., the volume ratio of the PVP-modified gold nanoparticle hydrosol to the 2-methylimidazolium methanol solution is 8:1). The other methods and steps are the same as in Example 1.

[0168] Comparative Example 6

[0169] The only difference between this comparative example and Example 1 is that in step S2, 0.2 g of 2-methylimidazole is dissolved in 20 mL of methanol to obtain a 2-methylimidazole methanol solution. The other methods and steps are the same as in Example 1.

[0170] Comparative Example 7

[0171] The only difference between this comparative example and Example 1 is that in step S2, 0.2 g of nickel nitrate hexahydrate is dissolved in 20 mL of methanol to obtain a nickel nitrate methanol solution. The other methods and steps are the same as in Example 1.

[0172] Application examples

[0173] (1) The scanning electron microscope image of the composite material obtained in Example 1 of the present invention is shown below. Figure 1 As shown, the flower-like morphology of the composite material can be observed; Figure 2 The transmission electron microscopy (TEM) images show that gold nanoparticles are encapsulated within the Ni-MOF, forming a core-shell structure. It is evident that this invention, while maintaining the flower-like morphology of the Ni-MOF material, introduces gold nanoparticles to prepare a flower-like composite material, thereby improving the material's light absorption capacity and consequently its hydrogen production performance. The scanning electron microscopy (SEM) and transmission electron microscopy (TEM) images of the composite materials obtained in other embodiments of this invention are similar to those in Example 1 and will not be shown here.

[0174] Gold nanoparticles are a type of noble metal plasmon material that exhibits localized surface plasmon resonance under illumination, macroscopically displaying excellent visible light absorption (e.g., ...). Figure 3 (As shown). A large amount of Ni is exposed on the flower-like Ni-MOF surface. 2+ Au nanoparticles can serve as catalytic active sites for the hydrogen evolution reaction. Introducing Au nanoparticles into the precursor solution of flower-like Ni-MOF allows for the epitaxial growth of Ni-MOF on the Au surface, resulting in a core-shell structured Au@Ni-MOF composite material (such as...). Figure 2 (As shown). Encapsulating gold nanoparticles inside flower-shaped Ni-MOFs can effectively improve the absorption capacity of Ni-MOFs in the visible light range (e.g., Figure 3 This leads to enhanced photoelectrocatalytic water splitting for hydrogen production.

[0175] (2) The composite materials prepared in Examples 1-10 and Comparative Examples 1-3 of the present invention were used to conduct photoelectrocatalytic water splitting hydrogen production experiments. The experimental procedure was as follows: 1 mg of the composite material was loaded on ITO conductive glass as the photoanode material for the photoelectrocatalytic reaction. Ag / AgCl was used as the reference electrode, Pt sheet was used as the counter electrode, and the electrolyte solution was 0.5 M sodium sulfate aqueous solution. The photoelectrocatalytic reaction was carried out in a 100 mL photoelectrocatalytic reactor with a bias voltage of 1 V (vs Ag / AgCl). The results are shown in Table 1 below.

[0176] Table 1

[0177] Example 1 16.94 3.39 Example 2 14.69 2.94 Example 3 15.12 3.02 Example 4 14.46 2.89 Example 5 16.53 3.31 Example 6 16.11 3.22 Example 7 10.56 2.11 Example 8 13.27 2.65 Example 9 10.32 2.06 Comparative Example 1 5.35 1.07 Comparative Example 2 0.76 0.15 Comparative Example 3 1.12 0.22 Comparative Example 4 5.47 1.09 Comparative Example 5 2.51 0.50 Comparative Example 6 0.62 0.12 Comparative Example 7 0.93 0.19

[0178] The experimental results of Example 1 and Comparative Example 1 are as follows: Figure 4 As shown, by Figure 4 It can be seen that the photoelectrocatalytic hydrogen production performance of the core-shell structure Au@Ni-MOF composite material in Example 1 of the present invention is more than 3 times that of the original Ni-MOF (Comparative Example 1).

[0179] Comparative analysis of the data in the table above shows that, compared to the original flower-like Ni-MOF, the introduction of gold nanoparticles effectively improves the photoelectric hydrogen production performance of the material. Meanwhile, the amount of gold nanoparticles introduced also has a certain impact on the performance of the composite material. When the amount of gold nanoparticles introduced is small, the improvement in the light absorption capacity of Ni-MOF is relatively small; when the amount of gold nanoparticles introduced is large, it will cause the gold nanoparticles to agglomerate. Therefore, the composite material exhibits the best performance when an appropriate amount of gold nanoparticles is introduced. Furthermore, the optimal hydrothermal conditions for preparing this composite material are 140℃ for 12 hours. Changes in the hydrothermal reaction temperature and time will also significantly affect the performance of the composite material; for example, changes in temperature can lead to a decrease in the crystallinity of the original Ni-MOF material or slight changes in its morphology.

[0180] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A method for preparing a core-shell structured Au@Ni-MOF composite material, characterized in that, Includes the following steps: S1, Preparation of PVP-modified gold nanoparticle hydrosol: Prepare aqueous solutions of chloroauric acid, sodium citrate, and PVP separately for later use. The aqueous solution of chloroauric acid was stirred and heated to boiling, and then an aqueous solution of sodium citrate was added. Stirring was continued to obtain a hydrosol of gold nanoparticles. PVP aqueous solution was added to gold nanoparticle hydrosol and stirred to obtain PVP-modified gold nanoparticle hydrosol. Preparation of S2 and Au@Ni-MOF composite precursor solutions: Take the PVP-modified gold nanoparticle hydrosol, centrifuge and wash with methanol, and finally disperse it in methanol to obtain a PVP-modified gold nanoparticle methanol solution for later use. Prepare 2-methylimidazolium methanol solution and nickel nitrate methanol solution for later use; A methanol solution of PVP-modified gold nanoparticles was mixed with a methanol solution of 2-methylimidazole and then subjected to ultrasonic treatment to obtain a 2-methylimidazole-Au methanol solution. 2-Methylimidazolium-Au methanol solution was added to nickel nitrate methanol solution and stirred continuously to obtain Au@Ni-MOF composite material precursor solution; In S2, the volume ratio of PVP-modified gold nanoparticle hydrosol to 2-methylimidazolium methanol solution is 2-5:1; the mass concentration of 2-methylimidazolium methanol solution is 2.5-3%, and the mass concentration of nickel nitrate methanol solution is 1-1.5%; the volume ratio of 2-methylimidazolium methanol solution to nickel nitrate methanol solution is 3:

4. S3. Preparation of core-shell structured Au@Ni-MOF composite materials: The Au@Ni-MOF composite material precursor solution was subjected to a solvothermal reaction. After the solvothermal reaction was completed, it was centrifuged and washed to obtain the product. The temperature of the solvothermal reaction was 130-150℃ and the reaction time was 10-14h.

2. The preparation method according to claim 1, characterized in that, The mass concentration of chloroauric acid aqueous solution in S1 is 0.005-0.01%; the mass concentration of sodium citrate aqueous solution is 1-2%. The PVP aqueous solution was prepared using PVP-K30, which has a relative molecular mass of 40,000 and a mass concentration of 2-3%.

3. The preparation method according to claim 1, characterized in that, In S1, the volume ratio of chloroauric acid aqueous solution to sodium citrate aqueous solution is 1000:7, and the volume ratio of gold nanoparticle hydrosol to PVP aqueous solution is 50:

1.

4. The preparation method according to claim 1, characterized in that, After adding sodium citrate to S1, the stirring time is 10-20 min; after adding PVP aqueous solution, the stirring time is 20-28 h.

5. The preparation method according to claim 1, characterized in that, In S2, the centrifugation speed is 11000 rpm and the centrifugation time is 5 min; the ultrasonic treatment time is 10-25 min and the stirring time is 0.5-2 h.

6. The preparation method according to claim 1, characterized in that, In S3, the centrifugation speed is 9000 rpm and the centrifugation time is 5 min.

7. A core-shell structured Au@Ni-MOF composite material, characterized in that, The core-shell structured Au@Ni-MOF composite material is prepared by the preparation method described in any one of claims 1-6.

8. The application of the core-shell structure Au@Ni-MOF composite material as described in claim 7 in the preparation of photoelectrode materials for photoelectrochemical water splitting to produce hydrogen.

Citation Information

Patent Citations

  • Method for preparing carboxyl functionalized gold nano core-shell structure MOF-5

    CN111320875A

  • Nanometer flower-shaped Ni-ZIF material as well as preparation method and application thereof

    CN115678028A